A pilot study exploring the relationship between the use of mobile technologies, walking distance, and clinical decision making among rural hospital nurses. (December 2019) - Sedgwick, Monique; Awosoga, Olu; Grigg, Lance
Providing evidence-based information at the point of care for time-poor nurses may lead to better clinical care and patient outcomes. Smartphone applications (apps) have the advantage of providing immediate access to information potentially increasing time spent with patients. This small-scale pre-post survey study explored the impact a smartphone app had on the distance nurses walked and their perceived clinical decision-making ability. A total of 20 nurses working in a rural hospital medical/surgical unit participated. The findings suggest that the use of the smartphone app did not decrease nurses' walking distance. Nor did using the app enhances nurses' perception of their clinical decision-making ability. However, there was a statistically significant increase in confidence in the app over time (F(1, 16) = 5.416, p = 0.033, partial η 2 = 0.253), suggesting that providing training opportunities including time to learn how to use smartphone applications has the potential to enhance nurses work.